Investigating Complications Associated With Occipital Nerve Stimulation: A MAUDE Study. Issue 3 (18th January 2018) - Doran, Joseph; Ward, Max; Ward, Brittany; Paskhover, Boris; Umanoff, Michael; Mammis, Antonios
Abstract : Objectives: The objectives of this study are to utilize the MAUDE data base to enhance our understanding of the complication profile for Occipital Nerve Stimulation, a therapy for which the current level of evidence is limited. Additionally, it is our objective to describe a systematic approach to processing the MAUDE data, which addresses its flaws and enhances its utility. Methods: From the FDA website, we accessed adverse events reports from the MAUDE data base for devices used in Occipital Nerve Stimulation between June 30, 2007 and June 30, 2017. All reports were sorted into an overall classification for types of adverse events, types of patient complaints, and types of specific device‐related complications. We then evaluated for the total number of adverse event reports that contained each of the patient complains and device‐related complications. Results: A total of 1233 adverse event records were obtained. Eight hundred twenty‐two records were classified as surgically manageable post‐operative complications, 121 as device malfunction, 29 as patient compliance issues, and 27 as intra‐operative complications. Two hundred thirty‐seven records were not classified. A total of 683 records contained patient complaints including 467 complaints of ineffective stimulation, 122 complaints of inappropriate or over‐stimulation, 50 complaints of device‐shock, and 44 complaints of IPG site pain. We found 581 post‐operative device‐related complications, which included 206 instances of lead migration, 157 reports of lead erosion, 155 infections, 46 lead‐fractures, and 17 lead disconnections. Conclusion: The MAUDE data base is a useful tool to investigate device related complications and helps fill the current gap in ONS data. Reviewing the types and frequencies of complications reported over the years allows clinicians with less personal experience to have a more realistic expectation of complications and make informed decisions based on the patient's unique needs. Additionally, patient complaint data are useful in establishing more realistic expectations for patient outcomes.